The comparison of different doses of magnesium sulfate to prevent myoclonus after etomidate induction [Etomidat sonrasi miyoklonusu önlemede farldi magnezyum sülfat dozlannin karşilaştinlmasi] - (:unkn) unknown (My University, 2010)
Aim: Myoclonic movements are common problems during induction of anesthesia with etomidate. Magnesium sulfate has been shown to reduce myoclonus after etomidate induction. This study aimed to compare different doses of magnesium sulfate to prevent etomidate-induced myocionus. Material and Methods: A prospective double-blind study was performed on 100 ASA I-III patients who were randomized into six groups. Magnesium sulfate in normal saline contained in coded 5 mL syringes was administered intravenously using the following dosages: Group 1, 0 mg; Group II, 300 mg; Group III, 600 mg; Group IV, 900 mg; Group V, 1200 mg; Group VI, 1500 mg. Ninety and 150 seconds after pretreatment with these dosages, etomidate 0,2 mg kg-1and vecuronium 0,1 mg kg-1 were injected, respectively. An anesthesiologist, blinded to the allocation of groups recorded myoclonic movements, pain, and sedation levels. Results: There were no significant differences between the groups with respect to age, body weight, gender, ASA physical status, types of the surgical operation performed, and comorbidities. Pretreatment with magnesium sulfate reduced the incidence and the severity of myoclonic movements after etomidate induction (P<0.05). Conclusion: Magnesium sulfate in dosages of 300 mg, 1200 mg, or 1500 mg administered 90 seconds before the induction of anaesthesia with etomidate is effective in reducing the severity of etomidate-induced myoclonus. We have concluded that the lowest dose (300 mg) of magnesium sulfate might be an alternative agent to prevent etomidate induced myoclonus.
Keywords: Etomidate; Magnesium sulfate; Myocionus